THE EFFECT OF THE APPLICATION OF PROGRESSIVE TAX RATES AND TAX SANCTIONS ON THE COMPLIANCE OF MOTOR VEHICLE TAXPAYERS IN SAMSAT MAKASSAR CITY - Hikmah, Nurul; Rabiyah, Ulfa; Apriandini Utina, Ratih (Entrepreneurship Undergraduate Program at Amkop Business School, 2024)
This research aims to determine the effect of implementing progressive tax rates and tax sanctions on compliance with motor vehicle tax obligations in the Samsat city of Makassar.Research II uses a quantitative approach by distributing questionnaires to vehicle users. The population in this study is motor vehicle taxpayers registered at SAMSAT Makassar II. So the researchers used 82 samples taken from this population. Hypothesis testing using the t test is carried out to see the significance of the influence of individual independent variables on the dependent variable by assuming that the other independent variables are constant.Results from this research. Progressive tax rates have a positive effect on taxpayer compliance in SAMSAT Makassar city. The research results show that the higher and fairer the progressive tariff, the higher the level of mandatory tax compliance in paying taxes. Tax sanctions have a positive effect on mandatory tax compliance in SAMSAT Makassar city. The results of this research show that the higher the sanctions given, the more taxpayers will be compliant in paying taxes, conversely the lower the sanctions given, the more taxpayers will be less compliant in paying taxes.